2010 Proceedings IEEE INFOCOM 2010
DOI: 10.1109/infcom.2010.5461970
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Practical Use of Network Tomography for Internet Topology Discovery

Abstract: Abstract-Accurate and timely identification of the routerlevel topology of the Internet is one of the major unresolved problems in Internet research. Topology recovery via tomographic inference is potentially an attractive complement to standard methods that use TTL-limited probes. In this paper, we describe new techniques that aim toward the practical use of tomographic inference for accurate router-level topology measurement. Specifically, prior tomographic techniques have required an infeasible number of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…In the network tomography literature, recent work in [28], [29] has also examined how to decrease the number of probes required to reconstruct logical tree topologies using delay-based methods. In contrast to this prior work, our TargetComplete methodology focuses on the reduction of the number of source-destination pairs used to probe the network using standard off-the-shelf TTL limited probing techniques (e.g., traceroute), not on the crafting of special probes to minimize measurement load.…”
Section: Related Workmentioning
confidence: 99%
“…In the network tomography literature, recent work in [28], [29] has also examined how to decrease the number of probes required to reconstruct logical tree topologies using delay-based methods. In contrast to this prior work, our TargetComplete methodology focuses on the reduction of the number of source-destination pairs used to probe the network using standard off-the-shelf TTL limited probing techniques (e.g., traceroute), not on the crafting of special probes to minimize measurement load.…”
Section: Related Workmentioning
confidence: 99%
“…One body of work developed techniques for inferring 1-by-N (i.e., single-source tree) topologies using endto-end measurements [7][8][9][10][11][12][13][14][15]. Follow-up work [1][2][3] showed that an M -by-N topology can be decomposed into and reconstructed from a number of two-source, two-receiver (2-by-2) subnetwork components or "quartets".…”
mentioning
confidence: 99%
“…1 More specifically, we start from the problem of 2-by-N topology inference, which is an important special case and can then be used as a building block for inferring an Mby-N . Consistently with [1], we assume that a (static) 1-by-N topology is known (e.g., using one of the methods in [4,[7][8][9][10][11][12][13][14][15]23]). Then we query the quartet component by sending end-to-end probes between the two sources and the two receivers, and we learn its topology using some of the methods in [1,2,16,17,[24][25][26][27][28] 2 .…”
mentioning
confidence: 99%
“…Network tomography in [16], [17] and [18] can be applied for discovering the network topology on the Internet, which is generally referred to as network topology identication. On the Internet, the network topology is hidden from us since complex heterogeneous domains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, Eriksson et al [18] advocate the practical use of tomographic inference for accurate router-level topology discovery. The authors developed a Depth-First Search (DFS) ordering algorithm that clusters end host targets based on shared infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%